Islamic Work Philosophy and Modern Urbanization: Ibn Khaldun's Perspective - Mukti, Titania; Ahyakudin; Sujai (ABHATS: Jurnal Islam Ulil Albab, 2025)
This research aims to reveal the concepts of Ibn Khaldun's thought, especially those related to economic life. The main focus of this study is Ibn Khaldun's contribution to economic philosophy. The method used is textual analysis based on primary sources, including works of interpretation and translation. The results of the study show that Ibn Khaldun, a prominent figure in Islamic thought, had a great influence on the development of modern economics. His monumental work, Al-Muqaddimah, deals with the relationship between human beings, especially Arab societies, in the context of the Arabic language. His contribution to economics can be understood through the perspective of Islamic history. The influence of Ibn Khaldun's thought on modern economic theory was significant, with far-reaching implications for contemporary thinkers and scholars. In his thoughts, Ibn Khaldun emphasized that work is an essential activity for humans in an effort to meet the needs of their lives. [Penelitian ini bertujuan untuk mengungkapkan konsep-konsep pemikiran Ibnu Khaldun, khususnya yang berkaitan dengan kehidupan ekonomi. Fokus utama dari kajian ini adalah kontribusi Ibnu Khaldun terhadap filosofi ekonomi. Metode yang digunakan adalah analisis tekstual berdasarkan sumber-sumber utama, termasuk karya tafsir dan terjemahan. Hasil penelitian menunjukkan bahwa Ibnu Khaldun, seorang tokoh terkemuka dalam pemikiran Islam, memiliki pengaruh besar terhadap perkembangan ekonomi modern. Karya monumental beliau, Al-Muqaddimah, membahas hubungan antara manusia, terutama masyarakat Arab, dalam konteks bahasa Arab. Kontribusi beliau terhadap ekonomi dapat dipahami melalui perspektif sejarah Islam. Pengaruh pemikiran Ibnu Khaldun terhadap teori ekonomi modern sangat signifikan, dengan dampak yang luas bagi para pemikir dan cendekiawan kontemporer. Dalam pemikirannya, Ibnu Khaldun menekankan bahwa bekerja adalah aktivitas yang esensial bagi manusia dalam upaya untuk memenuhi kebutuhan hidupnya.]